2005
DOI: 10.1038/sj.npp.1300891
|View full text |Cite
|
Sign up to set email alerts
|

Methamphetamine Causes Alterations in the MAP Kinase-Related Pathways in the Brains of Mice that Display Increased Aggressiveness

Abstract: Aggressive behaviors have been reported in patients who suffer from some psychiatric disorders, and are common in methamphetamine (METH) abusers. Herein, we report that multiple (but not single) injections of METH significantly increased aggressiveness in male CD-1 mice. This increase in aggressiveness was not secondary to METH-induced hyperactivity. Analysis of protein expression using antibody microarrays and Western blotting revealed differential changes in MAP kinase-related pathways after multiple and sin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
32
0
1

Year Published

2008
2008
2015
2015

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 48 publications
(36 citation statements)
references
References 71 publications
3
32
0
1
Order By: Relevance
“…One study in which mice were randomized to a chronic MA, acute MA, or control group revealed increased aggression in the chronic MA group. The authors further found evidence suggesting that such aggression may be due to disruption of the prefrontostriatal tracts, consistent with previous research in this area [9] . Another study comparing MA-dependent individuals with healthy controls found hyperactivity in the dorsal anterior cingulate cortex on functional magnetic resonance imaging and high self-ratings of hostility and interpersonal sensitivity in the MA group when exposed to fearful and angry faces [10] .…”
Section: Introductionsupporting
confidence: 79%
“…One study in which mice were randomized to a chronic MA, acute MA, or control group revealed increased aggression in the chronic MA group. The authors further found evidence suggesting that such aggression may be due to disruption of the prefrontostriatal tracts, consistent with previous research in this area [9] . Another study comparing MA-dependent individuals with healthy controls found hyperactivity in the dorsal anterior cingulate cortex on functional magnetic resonance imaging and high self-ratings of hostility and interpersonal sensitivity in the MA group when exposed to fearful and angry faces [10] .…”
Section: Introductionsupporting
confidence: 79%
“…The MAPK signaling pathway has been shown to regulate behavioral sensitization and addictive properties of drugs of abuse (Licata and Pierce, 2003;Sokolov and Cadet, 2006). In a recent study, Yan et al (2014) demonstrated that the casein kinase 2-inhibitor luteolin inhibited behavioral sensitization by blocking methamphetamine-induced MAPK activation in the caudate putamen of mice.…”
Section: Discussionmentioning
confidence: 98%
“…Experiments increasing extracellular levels of DA result in increased aggression, while the administration of DA antagonists decrease aggression (Kudryavtseva et al 1999;Sokolov and Cadet 2006). DA receptor knockout systems have also shown a reduced aggressive phenotype (Drago et al 1998;Miczek et al 2001).…”
Section: Introductionmentioning
confidence: 97%